ANALISIS FAKTOR – FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MENGGUNAKAN JASA LAYANAN EKSPEDISI POS INDONESIA - Muhammad Ali, Fikri; Ety Dwi, Susanti (Jurnal Bisnis Indonesia, 2021)
Pos Indonesia is a company engaged in goods delivery services that already have about24,000 service points that reach almost all sub-districts and villages/ villages, to remotelocations in Indonesia. This study explains what factors consumers consider in using PosIndonesia expedition services, which aims to know what factors influence consumers in usingPos Indonesia expedition services. Research method using quantitative research type, Factors - factors studied is marketingmix (7P). In this study, the population is Kebon Rojo Surabaya post office, while the sampleis as many as 100 respondents who have used Pos Indonesia expedition services. The sampleis obtained from unknown population formula with accidental sampling method that usescriteria to be considered as a sample (Purposive Sampling). The results of the calculation of factor analysis by including 18 variables obtained thatKMO measure of sampling adequency (MSA) of 0.858 and barlett's test of 672,998 with asignificance rate of 0.000. Based on the analysis of factors using rotation (varimax) it can beobtained manifest variables with a total of 4 new factors, namely consumer satisfactionfactors, service factors, consumer perception factors, and Branding factors. Of the 4 newfactors obtained, the four factors qualify as factors because they have an eign value of morethan 1, and the most considered variable is a comfortable waiting room variable. Keywords: Product Variations, Memorable Brand, Service Quality, Price Variants,Affordable Prices, Price According to Quality, Strategic Location, Easy to FindLocation, Interesting Ads, Promotions Through Social Media, Promotions ThroughBrochures, Employee Appearance, Employee Courtesy, Employee Responsiveness,Timely Delivery, Fast Claim Process, Comfortable Waiting Room, Cleanliness.  DOI : https://doi.org/10.33005/jbi.v12i1.2599